Effects of halloysite nanotubes (HNT) structures on antimicrobial activity on TPSS Film - Abuhamed, Nader; Ahmad, Zuraida; Tajuddin, Maisarah (Microscopy Society of Malaysia, 2020)
Halloysite nanotubes (HNT) build good interest in biological technologies attributable to their excellent loading capacity and hollow tubular structures. HNT is also naturally available, low toxicity, and inexpensive. This paper investigates the HNT structures' effect in encapsulating the antibiotics for antimicrobial activities in thermoplastic sago starch (TPSS) wound dressing film. The control TPSS film was produced using sago starch, glycerol, and water. In the nanocomposite films, the HNT was diluted in 0.25 and 0.5 mL, without and with immersion in 2 ml antibiotics, with a TPSS solution with the following names: TPSS/HNT/0.25, TPSS/HNT/0.5, TPSS/HNT/0.25A, and TPSS/HNT/0.5A, respectively. All samples were characterized by Fourier transform infrared, Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) for the morphological analysis and tested for antimicrobial activity using a disc diffusion test. Micrographs from SEM and TEM demonstrated that pristine HNT had an average length of 400 nm with an average outer and inner diameter of 90 nm and 30 nm, correspondingly. The HNT with empty lumen tubes shows high absorption and loading capability of the antibiotic. It is believed that the antibiotic was released over a prolonged time or responded to when the bacteria approached. The inhibition zone sizes designated the antimicrobial activity on nano-composites films were 67.3 ± 0.5 and 100 ± 0.3 mm2 for TPSS/HNT0.25 and TPSS/HNT0.5A, respectively, and zero inhibition zone for other samples.